Przyroda w mieście: pamięć czy zapomnienie? Przykład Coney Island w Nowym Jorku oraz Weißensee i Spreeinsel w Berlinie - Miściorak, Albert (Studia Etnologiczne i Antropologiczne, 2015)
The presence of nature in a city, especially one growing so spontaneously, has always aroused ambivalent feelings in its residents. Although, the city bears a yearning for “wild” nature (whose classic realization are English gardens), urban actions are aimed at keeping a safe distance from it. In contemporary cities “wild” nature appeared in the post-war ruins, post-industrial wastelands, peripheral cemeteries, etc. For many people, they are a symbol of degradation and oblivion, therefore, are often subjected to intensive restoration and conservation, which brings about liquidation of wildlife. But is it right? Have these places really lost all the power of recalling memories — these private and collective? In my speech, I will try to answer these questions, based on the study of a luna park in Coney Island (New York), Weißensee Jewish Cemetery (Berlin) and Spreeinsel — historical centre of Berlin.